Lipids by Yarrowia lipolytica Strains Cultivated on Glucose in Batch Cultures - Carsanba, Erdem (Microorganisms, 2020)
Oleaginous microorganisms, such as Yarrowia lipolytica, accumulate lipids that can have interesting applications in food biotechnology or the synthesis of biodiesel. Y. lipolytica yeast can have many advantages such as wide substrate range usage and robustness to extreme conditions, while under several culture conditions it can produce high lipid productivity. Based on this assumption, in this study, 12 different Yarrowia lipolytica strains were used to investigate microbial lipid production using a glucose-based medium under nitrogen-limited conditions in shake-flask cultivations. Twelve wild-type or mutant strains of Yarrowia lipolytica which were newly isolated or belonged to official culture collections were tested, and moderate lipid quantities (up to 1.30 g/L) were produced; in many instances, nitrogen limitation led to citric acid production in the medium. Lipids were mainly composed of C16 and C18 fatty acids. Most of the fatty acids of the microbial lipid were unsaturated and corresponded mainly to oleic, palmitic and linoleic acids. Linolenic acid (C18:3) was produced in significant quantities (between 10% and 20%, wt/wt of dry cell weight (DCW)) by strains H917 and Po1dL.